The effect of Indonesia's economic crisis on small farmers and natural forest cover in the outer islands - Sunderlin, William D.; Resosudarmo, I.A.P.; Rianto, E.; Angelsen, A. (Center for International Forestry Research, 2000)
Twenty million people live in or near Indonesia' s natural forests. The country's humid tropical forests are primarily in Sumatra, Kalimantan, Sulawesi, and Irian Jaya. A devastating regional economic crisis that began in mid-1997 affected Indonesia more strongly than any other country in Asia. A random sample survey of 1050 households was conducted in six outer island provinces to understand the effects of the crisis on the well-being of forest villagers and on their agricultural and forest clearing practices. In particular, the study sought to understand diverging opportunities introduced by the drastic depreciation of the Indonesian rupiah against the U.S. dollar; producers of agro-export commodities could obtain an income windfall from higher market prices but increased costs of living could neutralise potential income gains. Key findings are: (1) two-thirds of the households were worse off and only one-fifth were better off during the crisis than in the year before the crisis; (2) this happened despite three-quarters of households having export commodity income; (3) clearing of forest land increased slightly in the first year and greatly in the second year of the crisis; (4) land was cleared increasingly for export tree crops in sedentary systems and less for food crops in swidden cultivation systems; and (5) those who perceived themselves as worse off or better off were more likely to have cleared land during the crisis, and to have cleared a larger area of land, than those who felt their well-being did not change significantly. Forest villagers perceived themselves as worse off during the crisis than before. Moreover, there is increased pressure on the forests despite increased sedentary farming during the crisis. Key policy lessons are: (1) farmers need assistance in diversifying their income sources to protect against possible future economic shocks; and (2) there should be greater awareness of how macroeconomic instability can lead to undesirable environmental consequences.